(untitled) (Globalization and Business, 2023)
This article investigates the link between commercial bank risk-taking and various factors. I use a panel data model to look at bank-specific and macroeconomic factors in order to evaluate bank risk-taking using sample evidence from Georgian commercial banks. The time span chosen, 2006-2014, considers the impact of the country’s persistent financial and economic difficulties. I look at capitalization, efficiency, capital structure, size, profitability, non-deposit financing, economic growth, revenue diversification, industry concentration, interest rates, inflation, and as variables that influence bank risk.